Bridging the research‐policy gap: the importance of effective identity leadership and shared commitment. (1st February 2020) - Mols, Frank; Bell, Jennifer; Head, Brian
Abstract : It is widely agreed that the availability of high quality evidence does not translate readily into influence over policy decisions. This insight has generated long-running debates about the most effective way to 'bridge the gap' between policy research and policymaking, and to increase policy research 'uptake'. The proposed remedies (for example, greater 'linkage and exchange activity', 'knowledge brokering', 'joint knowledge production') tend to be premised on the idea that increased contact will increase preparedness to take on board other stakeholders' views. We agree that contact is important, along with adequate resourcing and access to good quality research evidence. However, as social and organisational psychologists have shown, trust and mutual understanding do not automatically emerge from more intensive interaction, but require effective 'identity leadership', to ensure core values (about shared goals and directions) become internalised in new shared self-understanding. So far, these insights have been neglected in the evidence-based policy literature, and the purpose of this paper is to fill this gap. More specifically, we draw on social-psychological research into 'identity leadership', and use illustrative data from interviews with leaders in public agencies and a major NGO partnership, to show (a) that leaders play an important role embedding commitment to evidence-based policy into 'organisational culture'; and (b) that leaders of successful partnerships go to great lengths to unite stakeholders and to promote a shared (overarching) sense of purpose and 'mission'.